Construction and maintenance of membrane roof covering / Ahmed Daniel Jamil - Jamil, Ahmed Daniel (2008)
This is a routine report that student in the final year need to do in order to let them graduate. This report is based on the research that choose by the student that might influenced by the current problem in the construction industry. The report that I’ve choose is based on the feasibility studies of the construction and maintenance of tensioned roof covering. In this report will explain the construction of membrane roof in the local industry and how it to be maintains. As we all know, the usage of tensioned roof covering in Malaysia is very limited due to lack of knowledge in some of the contractor and developer. So the purpose of this report is to broaden the mind of accepting this type of roof in the local industry. Maintenance works done are also stated in this report based on 2 case studies located in the Klang Valley. Each building has its own standard of maintenance so the work for maintenance might be different. Even though it different it still need to follow the same regulation and building law that are stated in this report.